First Experience of Laser Radiation Application in Wound Treatment After Open Hemorrhoidectomy - S. A. Frolov; D. V. Vyshegorodtsev; A. M. Kuzminov; V. Y. Korolik; A. R. Melkumyan; M. A. Ignatenko; I. V. Vorobjeva; S. G. Magomedova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to improve treatment outcomes for patients after open hemorrhoidectomy. Materials and methods. The results of treatment of 62 patients after open hemorrhoidectomy by ultrasonic scalpel, who were randomized into the main and control groups, 31 persons in each group, were analyzed. The patients of the main group underwent dressing of postoperative wounds using water-soluble ointments in combination with laser irradiation daily from day 2 after the surgical intervention and further on days 14, 21 and 30. In the control group only dressing with the use of water-soluble ointments was performed. In the postoperative period the terms of wound healing were determined based on the data of visual inspection, anoscopy, planimetric and cytologic methods of examination. Microbiological (culture) examination, assessment of pain syndrome intensity using visual analog scale on days 1–7, 14, 21, and 30 after surgical treatment and quality of life using SF-36 questionnaire before hemorrhoidectomy and on day 30 after it were also performed. Results. On day 30 wound healing occurred in 29/31 (94 %) patients of the main group and only in 5/31 (16 %) patients of the control group (p < 0.001). The growth of microorganisms in the main group was noted on day 2 in 31/31 (100 %) cases, on day 21 — in 20/28 (71 %) cases (p = 0.001); in the control group: on day 2 — in 27/31 (87 %), on day 21 — in 30/31 (97 %) cases, although the significance of differences was not achieved (p = 0.4). The level of pain syndrome was already lower from the second day after surgical treatment in patients of the main group and amounted to 5 (4; 6) points, in the control group — 6 (5; 7) (p = 0.016), and on day 30 — 0 (0; 0) points in the main group and 1 (0; 2) point in the control group (p < 0.001). Before treatment, the groups were comparable in quality of life; on day 30, statistically significant differences were noted in three indicators: physical functioning (PF) — 80 (75; 93) points in the main group vs. 80 (70; 80) points in the control group (p = 0.041); the criterion of role functioning due to emotional state (RE) — 100 (66; 100) points vs. 66 (17; 67) points (p = 0.002), and the criterion reflecting the intensity of pain and its impact on daily activities (BP) — 51 (37; 62) points vs. 41 (22; 51) points (p = 0.023). Conclusion. Application of laser therapy after hemorrhoidectomy with ultrasonic scalpel promotes stimulation of reparation processes, shortening of postoperative wound healing time, reduction of bacterial contamination of wounds, reduction of pain syndrome intensity and improvement of quality-of-life indicators in patients of the main group in comparison with the control group.